Does trade integration matter for reducing intra-regional disparities? ASEAN evidence from a panel co-integration approach - PHAM Thi Hong Hanh (FIW - Research Centre International Economics, 2009)
Needless to say, it is necessary to study the relative scales of the trade creation effect and the trade diversion effect to evaluate success of ASEAN trade integration and to determine whether or not the intra-bloc trade share is appropriate as an indicator of the progress of reducing intra-regional disparities in ASEAN. Therefore, this paper first uses descriptive statistics and some key indicators to track the progress in economic growth and in trade integration that is the main pillar of building ASEAN Economic Community. Second, we make an attempt to provide answers to the question of whether trade integration matters for reducing intra-regional disparities among ASEAN member states over the period 1995-2007. We perform the panel co-integration method developed by Pedroni (1999) that allows for heterogeneity across ten ASEAN countries. Our major finding shows that trade integration, which is captured by intra-regional exports and imports flows, is appropriate as an indicator of progress of reducing income disparities in the ASEAN zone. Finally, applying the General Method of Moments (GMM) estimation, we also find that deepening of intra-regional trade integration creates more trade flows among ASEAN member states without diverting trade flows with non-members.
Keywords: F13; F15; O18; O19; O47; O57; 330; Growth; Trade Integration; Intra-regional disparities; Co-integration; ASEAN